Pengaruh Proporsi Bidang Gambar-Tulisan Dalam Iklan Layanan Masyarakat Dan Keterlibatan Pribadi Terhadap Rekognisi - Perpustakaan UGM, i-lib ([Yogyakarta] : Universitas Gadjah Mada, 2004)
This study examines the proportion effect of picture-written on the public service advertisement and the personal involvement upon recognition. The research is experimental, involving 40 university students as its research subject. They are categorized into two groups: 20 persons are categorized as high personal involvement and 20 persons are low personal involvement. The subject is divided into two groups, each group consists of 20 persons (10 persons are high personal involvement and 10 persons are low personal involvement). The instrument which is used is public service advertisement (the proportion of picture : written = 70 %:30 % and picture : written = 30 %:70 %). Each groups is treated twice in different times and after that they do a recognition test. The collected data are analyzed Quantitatively by using SPS-2000 program of Sutrisno Hadi and Yuni Pamardiningsih, IBM/IN version, copyright Â© 2000. The results show that: (1) personal involvement factor does not determine recognition, although the message delivered deals with her/his involvement. The higher personal involvement is not followed by the high recognition score